Project management applications of the theory of constraints beyond critical chain scheduling - Steyn, H. (International journal of project management, 2002)
The application of the Theory of Constraints (TOC) is an approach that can be used to develop a variety of management techniques. As a result of the multi-disciplinary nature of project management a variety of different applications within project management are possible. The application of the TOC approach to project scheduling led to the development of the “critical chain” technique that has been the subject of discussions in literature. This paper explains why TOC was initially applied only to project scheduling. A second application of TOC is to manage resources shared by a number of concurrent projects. The basic principles of this second application are discussed in this paper. In addition to the above-mentioned two applications the TOC approach can also be applied to other areas of project management such as project cost management and project risk management.